2009
DOI: 10.1590/s0080-62342009000400027
|View full text |Cite
|
Sign up to set email alerts
|

Enfermidades tratadas e tratáveis pela acupuntura segundo percepção de enfermeiras

Abstract: Portuguese / English: www.scielo.br/reeusp RESUMO Esse trabalho objetivou identificar e analisar as percepções dos enfermeiros acerca das enfermidades tratadas e tratáveis pela acupuntura. Foram consideradas: (1) as enfermidades das entrevistadas que já haviam se submetido ao tratamento com acupuntura; (2) as enfermidades que as enfermeiras têm e que poderiam ser tratáveis pela acupuntura; (3) sugestões de doenças tratá-veis pela acupuntura para o paciente de Unidades de Saúde. Pesquisa de natureza exploratóri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 5 publications
0
4
0
14
Order By: Relevance
“…It aims to relieve symptoms via the reorganization of the body's energy, with the goal of self-cure 18 - 19 . Sham acupuncture (SA), also called placebo, may be considered a fake intervention, as it is performed off the acupuncture points established by TCA 20 - 21 .…”
Section: Introductionmentioning
confidence: 99%
“…It aims to relieve symptoms via the reorganization of the body's energy, with the goal of self-cure 18 - 19 . Sham acupuncture (SA), also called placebo, may be considered a fake intervention, as it is performed off the acupuncture points established by TCA 20 - 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Orpheu et al 42 detected a time dependent increase in the demand for body contour surgery in massive weight loss patients from pretreatment through bariatric surgery and subsequently over a three-year follow up. Kurebayashi et al 43 analyzed nurses' perceptions about diseases that are treated by acupuncture and found that it was used to treat obesity among other morbid situations.…”
Section: Methodsmentioning
confidence: 99%
“…Según los estudios analizados en la presente revisión, la utilización de las PIC viene aumentando significativamente en el tratamento de diversas enfermedades. Estudios muestran resultados positivos en la reducción de los niveles de ansiedad, de síntomas depresivos, de estrés, de alívio del dolor, y de la ingesta compulsiva (17)(18)(19)(20)(21)(22) . Los individuos participantes de las investigaciones señalaron como programas de terapias …”
Section: Categoría 1: Prácticas Integradas Complementarias Como Terapunclassified
“…El MBSR fue más eficaz en el aumento de la atención y de la energía para la reducción del dolor. más utilizadas en el control de estas enfermedades: Mindfulness Based Stress Reduction (MSBR), y Cognitive-Behavioral Stress Reduction (CBRS), y como terapias: Kouk Sun Do, la acupuntura, la meditación, la respiración controlada, el yoga, la imaginación y la terapia de la polaridad (17,(19)(20)(21) .…”
Section: /Estadosunclassified
See 1 more Smart Citation